(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students’ attention in learning is one of the factors that influence the success in implementing learning. The implementation of learning is not fully planned, it is evident in the implementation of learning that many students do not focus or pay attention to learning. Poor student attention will be one of the causes of failure in achieving learning objectives. The data analysis prerequisite test was conducted using normality and linearity tests. The hypothesis testing was done using a simple linear regression analysis. The result of research showed that the data of learning and learning achievement was valid, reliable, and distributed normally. Effect of learning attention on the learning achievement i wasindicated by sig(p) < α or 0.000 < 0.05. Learning attention contributed to the learning achievement of Buddhism education by 45%.